Analysis of the Effect of Using Marketplace Based on Customer Data Security - Rizki Dewantara; Wilda Widiawati; Pandu Adi Cakranegara; Abdul Samad Arief; Tienni Mariana Simanjorang (Jurnal Mantik, 2022)
The era of the digital economy has become a trend that facilitates transactions for all individuals. One of them is the existence of a marketplace application that uses the internet network to facilitate the buying and selling process. Currently, numerous individuals use the functionality and convenience of the marketplace application for their various activities and needs. Obviously, the features and convenience of the marketplace application have been significantly adapted to meet the needs of customers, and customer data security has been prioritized. This study examines the level of customer understanding regarding the security of personal data when conducting online transactions and utilizing marketplace applications. Random sampling was used to distribute questionnaires containing 16 questions with guttman scale assestment about environmental and social influences, personal data security facilities, the purpose of using the marketplace, and self-awareness regarding customer data security when using the marketplace application to 80 respondents. 84% of customers stated that the security of their personal data has been entrusted to the used marketplace application, according to the overall findings of the study. Obviously, this is related to the customer's needs in utilizing marketplace features, as 77.5% of customers strongly believe that the marketplace application they use provides a level of security for customer personal information.